Penggunaan Multimedia Interaktif Untuk Meningkatkan Kemampuan Penguasaan Konsep IPA - Muldiyana Nugraha; Ari Fajria Novari (Universitas Mathla'ul Anwar Banten, 2018)
This study aims to analyze the idea of ​​using interactive multimedia in improving students' mastery of concepts in science lessons. Research using quantitative methods with the method quasi-experimental. The study design is nonequevalent control group design. The steps taken in this research are: determining the sample, held a pretest, providing treatment in experimental and control groups, and provide a posttest. Based on the results of research can be concluded that there are positive and significant difference between the ability of students' mastery of the concept of an optical instrument that uses interactive multimedia learning with learning that uses Microsoft Office PowerPoint on science lessons. The use of interactive multimedia in learning can also enhance students' interest and motivation in learning to follow. Generally speaking, the use of interactive multimedia and significantly effective in improving the ability of mastering the concept of optical tools in the classroom science lesson VIII.